In vivo Metabolic Investigation of Oxygen, Light, and Temperature Effects on Dormancy Alleviation of Sesame (Sesamum indicum L.) Seeds - Yingqiang Cai; Xianqin Wu; Mengting Chen; Yumin Wan; Xiayi Ruan; Honghao Cai (Journal of Agricultural Sciences)
As an edible seed, sesame seeds require careful storage to maintain their quality. Dormancy helps seeds extend their lifespan by slowing down metabolic processes, reducing energy consumption and natural aging. However, seeds may exit dormancy and begin germination during storage due to variations in temperature, light, and oxygen conditions. This transition is not easily visible, but nutritional components within the seeds can start to deplete. In this study, non-invasive magnetic resonance spectroscopy and imaging were used to monitor sesame seeds stored under different temperature, light, and oxygen conditions for over 120 hours. Results showed that seeds remained dormant at 15 °C under oxygen deprivation and in the absence of light. When exposed to continuous light at 15 °C, under anaerobic or aerobic conditions, changes in metabolic resonances were observed through spectroscopy, indicating moisture and fatty acid transfer between seed structures. Despite these changes, magnetic resonance imaging showed that the embryo did not develop. At 24 °C with continuous light and aerobic conditions, both spectroscopy and imaging analyses revealed significant metabolic changes, and all internal seed structures developed normally, with visible signs of germination. This study highlights that although sesame seeds are non-photoblastic, light can still trigger metabolic activity within the seeds, while suitable temperature is essential for complete seed development. These findings provide valuable insights into the dynamic molecular-level metabolic changes from dormancy to early seed germination using magnetic resonance technology and offer guidance for maintaining seed dormancy during storage.